Alginates Recent Uses of This Natural Polymer - Pereira, Leonel (Biochemistry, 2020)
Alginates are polysaccharides found in both the intercellular matrix of brown algae and extracellularly covering some species of bacteria. Alginate varies in composition of the algae from 20% to 60% dry matter, but on average brown algae species has 40% alginate. Alginate from brown algae occurs as gels containing sodium, calcium, strontium, magnesium, and barium ions. They are widely used by the food industry, giving foods texture properties such as thickening, adhesion, emulsification, gelling, or fullness. This book covers the latest uses of this phycocolloid in the pharmaceutical, medical, and technological fields, namely bioink for 3D bioprinting in tissue engineering and regenerative medicine, and the application of artificial intelligence in modern healthcare systems.